Qualitative case study investigating PAX-good behaviour game in first nations communities: insight into school personnel's perspectives in implementing a whole school approach to promote youth mental health. Issue 9 (26th September 2019) - Wu, Yu Qi; Chartier, Mariette; Ly, Gia; Phanlouvong, Ari; Thomas, Shelby; Weenusk, Jonathon; Murdock, Nora; Munro, Garry; Sareen, Jitender
Abstract : Objectives: PAX-Good Behaviour Game (PAX-GBG) is associated with improved mental health among youth. First Nations community members decided on a whole school approach to facilitate PAX-GBG implementation, by offering intervention training to all staff members in their schools. Our objective is to gain a greater understanding of how this approach was viewed by school personnel, in order to improve implementation in remote and northern First Nations communities. Design: We conducted a qualitative case study using semi-structured interviews. Setting: Interviews were conducted in First Nations schools located in northern Manitoba, Canada, in February 2018. Participants: We used purposive sampling in selecting the 23 school staff from First Nations communities. Intervention: PAX-GBG is a mental health promotion intervention that teachers deliver in the classroom alongside normal instructional activities. It was implemented school-wide over 4 months from October 2017 to February 2018. Outcome measures: We inquired about the participants' perception of PAX-GBG and the whole school approach. We applied an iterative coding system, identified recurring ideas and classified the ideas into major categories. Results: Implementing the PAX-GBG whole school approach improved students' behaviour and created a positive school environment. Students were learning self-regulation, had quieter voices and demonstrated awareness of the PAX-GBG strategies. All teachers interviewed had used the programme. Support from school administrators and having all school personnel use the programme consistently were facilitators to successful implementation. Challenges included the timing of training, lack of clarity in how to implement and implementing among students in older grades and those with special needs. Conclusions: The whole school approach to implementing PAX-GBG was viewed as an acceptable and feasible way to extend the reach of PAX-GBG in order to promote the mental health of First Nations youth. Recommendations included ensuring school leadership support, changes to the training and cultural and literacy adaptations.